The value of travel time savings and the value of leisure in Zurich: Estimation, decomposition and policy implications. (August 2021) - Schmid, Basil; Molloy, Joseph; Peer, Stefanie; Jokubauskaite, Simona; Aschauer, Florian; Hössinger, Reinhard; Gerike, Regine; Jara-Diaz, Sergio R.; Axhausen, Kay W.
Abstract: We use state-of-the art estimation approaches to obtain mode-specific values of travel time savings (VTTS) based on pooled RP/SP travel choice data of Zurich workers. Unlike the large majority of time valuation studies, we also have data on the respondents' time-use and expenditure allocation, which enables us to estimate their value of leisure (VoL), i.e. the opportunity value of liberated time when the duration of a committed activity, such as travel, is reduced. We use the estimates of the VoL and the VTTS to derive the value of time assigned to travel (VTAT) – the monetary value of the direct (dis-)utility derived from the conditions experienced while traveling. Linking the VTTS and VoL at the individual-level allows for a detailed analysis of VTAT distributions. We obtain median VTTS for car and motorbike (MIV) of 30.6 CHF/h, carpooling (CP) of 27.7 CHF/h, carsharing (CS) of 26.7 CHF/h, walk of 26.7 CHF/h, bike of 18.2 CHF/h and public transportation (PT) of 14.8 CHF/h. The median VoL amounts to 25.2 CHF/h. We find that MIV, CS and CP perform worst in terms of VTAT (as indicated by values smaller than zero), showing that the perceived travel comfort all in car modes (private, shared and pooled) is substantially lower than for PT and bike, where the VTAT are greater than zero. From a transportation policy perspective, our results suggest that travel comfort matters greatly and investing in the quality of travel should therefore obtain more attention. However, from a PT operator's point of view, our results indicate that in the case of Zurich, investing in faster connections may exhibit a higher marginal impact on user benefits, since the VoL is relatively high, while travel comfort is perceived as high already. Highlights: Value of leisure and value of travel time estimated for the same respondents Value of time assigned to travel is obtained for each mode and individual Improved policy recommendations when obtaining all value of time components Inclusion of income savings in the time-use and expenditure allocation model Inputs for researchers collecting data on time-use and expenditure allocation